The promising cultivars of spring oats, adapted to the climatic conditions of the arid part of the North PreCaspian - V. A. Fedorova; T. V. Mukhortova; E. G. Myagkova (Зерновое хозяйство России)
Oats is the most essential food and grain forage crop in Russia. At present due to the active and fast development of husbandry and food industry there is a great need in oats grain that can be used both as fodder and as food. A good fodder pool is of great importance for further development of husbandry, its improvement and productivity, where grain forage crops are greatly significant as the sources of concentrated and coarse fodder (roughage). The agro ecological variety testing conducted by FSBSI “PreCaspian RI of arid agriculture” in 2014-2016 allowed selecting the promising varieties of spring oats, which meet all requirements to productivity, possess high qualitative grain characteristics and have adaptability to dry conditions of the North PreCaspian. The work presents the data about weather conditions during the study, gives the information about the selected promising varieties of spring oats ‘Konkur’, ‘Lev’ and ‘Borets’ with 1.0-1.3 t/ha of grain productivity, 75.0-80.1 cm of plant height, in comparison with the standard variety ‘Lgovsky 1026’ with 0.68 t/ha of grain productivity, 65.5 cm of plant height. The new cultivars of oats possess 80-84 days of vegetation period, 35.3-36.4 g of 1000-kernels weight, when the standard variety ‘Lgovsky 1026’ possesses 88 days of vegetation period and 32.4 g of 1000-kernels weight. All three cultivars are tolerant to lodging. According to the results of study these varieties are recommended to cultivation on light chestnut soils of the arid part of the North PreCaspian.